Fundamentos y aplicaciones del análisis de correspondencias difuso (2012)
Fuzzy correspondence analysis is a method quite useful, but little known in our country. In this paper we review the current literature, summarize the methods and look for some applications. Finally, we present an example to analyze the socioeconomic proﬁles in a group of students, comparing the multiple correspondence analysis with fuzzy analysis. In this way, it is shown the usefulness of the fuzzy analysis when the information is summarized and it is taken into account the main diﬀerences and similarities between the two methods.